Types of Co-Opetition among Local Government Units in Polish Metropolitan Areas - Koszel, Maciej; Bartkowiak, Piotr (Studia Oeconomica Posnaniensia, 2017)
The article deals with the problem of shaping inter-organizational relations in the context of their cooperation and competition (known also as coopetition) between local government units. Empirical research was conducted in 2015/2016 with the example of self-government units in Polish metropolitan areas. An assumption was made, that the dominant approach used in that matter is cooperation. The main objective of the paper was to 1) prepare a typology of coopetition among chosen units and 2) identify the dominant type. A questionnaire was used as a main research tool, dedicated and addressed to the representatives of local government unit’s authorities.